A proteção de dados do consumidor no ambiente digital: a utilização da LGPD na mitigação de fraudes bancárias - Vasconcelos, Marta Barros (2023)
Over the past few years, the advancement of technology has had an increasing impact on society, also greatly influencing the law in view of the need to keep up with the changes suffered at the same speed. Consumer protection, in this technological context, encountered major challenges with the increasingly intense digitization of consumer relationships. The protection of personal data, in turn, is shown to be a great touchstone to be protected by law, due to the sharing of data in an increasingly vigorous way in the digital society, even becoming a fundamental right to from Constitutional Amendment n. 115. Given these fundamental bases, the problem addressed by the research arises: the growing number of frauds committed against consumers, through the misuse of their personal data in the provision of digital banking services (or internet banking), could be mitigated with the arrival of legislation with specific purpose of protecting this new right, as is the case with the LGPD? By approaching the intrinsic relationship between the fundamental rights of consumer protection and personal data protection, this study aims to analyze the limits and possibilities of using the provisions brought by the LGPD in the provision of virtual banking services, as a way of better guaranteeing the protection of the consumer. consumer, a vulnerable part of the consumption relationship, in cases of damage caused by bank fraud. In this way, the protection of personal data of the individual in the digital sphere is shown as a starting point for the problem of fraud practiced in the digital banking environment, through its appropriation and misuse, to be better solved. From this perspective, in addition to addressing the problem of improperly obtaining personal data due to non-compliance with the duty of custody and due treatment, in the manner recommended by the LGPD, the study will also seek to understand the need for accountability of banking service providers through the application of the understanding signed by the STJ in summary no. 479, using the risk-benefit theory. Through the use of documentary research and the hypothetical-deductive method, in view of the investigated problem (threat of the aforementioned fundamental rights), the need for joint use of the provisions of the LGPD and the CDC was observed, through the use of the theory of dialogue from the sources, in the search for full protection of the consumer, against bank fraud suffered through the improper use of their personal data in digital banking contracts.